COMPARATIVE ANALYSIS OF DIFFERENT THREAD DEPTHS OF SHORT IMPLANTS IN REHABILITATION OF ATROPHIC POSTERIOR MAXILLA - Ibraheem Mahmoud Mwafey; Ahmed Mohammed Saaduddin Sapri; Ahmed Abdelmohsen Younis Ahmed Ali (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim: the current study aimed to assess the performance of deep-threaded and conventional-threaded short implant in the rehabilitation of atrophic posterior maxillary region.Methods: This randomized controlled clinical trial included 14 patients (6 males and 8 females, ages 37-60) recruited from Al-Azhar University who required implants in posterior maxillary region with residual bone height of 6-8 mm. Clinical assessments and CBCT imaging were used during the preoperative evaluation to determine bone height and density. Implants were inserted under local anesthetic, and osteotomies were made with OXY KIT drills. Osstell ISQ was used to assess the implant stability from the buccal and mesial directions. Clinical and radiographic evaluations, including CBCT imaging for crestal bone loss and bone density were carried out immediately and after six months.Results:  The study findings revealed non-significant differences in both age and gender distributions between the groups. There were no incidences of infection or implant failure documented, indicating a 100% success rate. Group II (deep-threaded implants) had significantly higher primary stability and periimplant bone density immediately after surgery than Group I, although secondary stability at six months was comparable between the two groups. Both groups showed considerable improvements in bone density over time, with Group II maintained higher levels.Conclusion: Deep-threaded short implants offer superior primary stability and peri-implant bone density, while both implant types achieved similar secondary stability and improved bone density over time, making deep-threaded implants ideal for atrophic posterior maxilla challenging cases.